2021
DOI: 10.3168/jds.2020-19387
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for cheese-making traits in Spanish Churra sheep

Abstract: The global production of sheep milk is growing, and the main industrial use of sheep milk is cheese making. The Spanish Churra sheep breed is one of the most important native dairy breeds in Spain. The present study aimed to estimate genetic parameters for a wide range of traits influencing the cheese-making ability of Churra sheep milk. Using a total of 1,049 Churra ewes, we studied the following cheese-making traits: 4 traits related to milk coagulation properties (rennet coagulation time, curd-firming time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
3
15
1
Order By: Relevance
“…Moreover, to our knowledge, there are no studies that combine analyses of GWAS for milk and cheese-making traits in 2 different dairy breeds. Different breeds show different behaviors concerning MCP (Pazzola et al, 2014a;Pelayo et al, 2021). In particular, concerning Assaf and Churra sheep, previous studies performed by our research group have identified clear differences between both breeds regarding MCP.…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Moreover, to our knowledge, there are no studies that combine analyses of GWAS for milk and cheese-making traits in 2 different dairy breeds. Different breeds show different behaviors concerning MCP (Pazzola et al, 2014a;Pelayo et al, 2021). In particular, concerning Assaf and Churra sheep, previous studies performed by our research group have identified clear differences between both breeds regarding MCP.…”
Section: Introductionmentioning
confidence: 62%
“…The phenotypic data used in this study were previously described by Sánchez-Mayor et al (2019) for the Assaf breed and by Pelayo et al (2021) for the Churra breed. A total of 2,020 ewes belonging to the Assaf (n = 1,039, number of flocks = 4) and Churra breeds (n = 981, number of flocks = 2) were analyzed.…”
Section: Sampling Genotyping and Quality Filteringmentioning
confidence: 99%
See 3 more Smart Citations